Algoritma C4.5 Untuk Klasifikasi Jenis Kekerasan pada Anak (Kasus DP3A Kabupaten Karawang) - Eshardiansyah, Raka Putra; Sulistiyowati, Nina; Jajuli, Mohamad (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Kabupaten Karawang is an area ranked 3rd as an area that has the potential to be prone to violence against children. Every year from 2016 to 2020 always shows an increasing number every year. Classification with data mining by applying the 4.5 algorithm is expected to be a solution to reduce the number of violence against children in Karawang Regency. The data that has been obtained is validated using k-fold cross validation and then evaluated using a confusion matrix and ROC curve. The C4.5 algorithm can be used to classify data on violence against children in Karawang Regency and get good results. The results of the confusion matrix using 60:40 split data on the violence dataset in children in Karawang Regency produce an accuracy value of 82.8125%, a precision value of 96.8% and a recall value of 90.5%. While the evaluation with the ROC curve with the classification quality "Good Classification" of 0.897. The 70:30 data split method was evaluated with the confusion matrix, resulting in an accuracy value of 93.2432%, precision of 94.5% and recall of 87.5%. While the evaluation with the ROC curve with the classification quality "Excellent Classification" of 0.953. The 80:20 data split method was evaluated with the confusion matrix, resulting in an accuracy value of 92.9142%, a precision of 91.7% and a recall of 81%. While the evaluation with the ROC curve with the classification quality "Excellent Classification" of 0.941.